Drinking water as a risk factor to poultry health - Amaral, LA do [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
In the poultry industry, the use of water with adequate physical, chemical and microbiological quality it is of fundamental importance. Since many birds have access to the same water source, quality problems will affect a great number of animals. The drinking water plays an important role in the transmission of some bacterial, viral and protozoan diseases that are among the most common poultry diseases. Important factors to prevent waterborne diseases in broiler production are the protection of supply sources, water disinfection and the quality control of microbiological, chemical and physical characteristics. Water is an essential nutrient for birds and therefore quality preservation is fundamental for good herd performance. The farmer may prevent many diseases in bird flocks by controlling the quality of the ingested water, will certainly result in decreased costs and increased profit, two essential aims of animal production nowadays.
Keywords: microbiological quality; poultry industry; water